Somatosensory evoked potentials as a screening tool for diagnosis of spinal pathologies in children with treatment refractory overactive bladder - DAĞÇINAR, ADNAN; ULUÇ, KAYIHAN; BAYRİ, YAŞAR (SPRINGER, 2017)
Purpose To evaluate the usefulness of somatosensory evoked potential as a screening tool for spinal pathologies in patients with treatment refractory overactive bladder. Methods This prospective study was performed between January 2011 and January 2014. Children > 5 years old with treatment refractory overactive bladder were enrolled after exclusion of anatomical and neurological causes of incontinence. All patients underwent urodynamic studies, spinal MRI, and somatosensory evoked potential (SEP). Sensitivity, specificity, PPV, and NPV were calculated for SEP. Results Thirty-one children (average age 8.3 +/- 2.9 years) were included in the study. SEP was abnormal in 13 (41.9%), and MRI was abnormal in 8 (25.8%) patients. SEP was found to have a sensitivity of 87.5%, a specificity of 73.9%, positive predictive value of 53.85%, and negative predictive value (NPV) of 94.4%. Conclusion In patients with treatment refractory OAB, SEP is an important tool for the screening of tethered cord/spinal pathologies. Our results suggest that a child with a normal SEP study in this group of patients may not require further investigation with MRI.
Keywords: Occult spina bifida; Sensory evoked potential; Urinary incontinence; ELECTRICAL NERVE-STIMULATION; FILUM TERMINALE; DYSFUNCTION